The American automobile frenzy of the 1950s - Offer, A (University of Oxford, 1996)
A pronounced cycle of car sales in the 1950s is explained in terms of styling competition and consumer preferences. An oligopolistic industry concentrated on non-price competition, and responded to perceived consumer demand for styling and status, with an accelerated product cycle. Demand was shifting from higher price-and-status models, to the feature-loaded high end of 'low-price' models. This suggests a consumer preference for sensual gratification rather than status. But feature competition was eventually constrained by the physical limitations of car size and power, which created a competitive impasse. Upwards feature drift also opened up a gap at the bottom of market. This gap was invaded by imports. Consumer feature fatigue was expressed in buyers' strike in 1958, but Detroit responded nimbly with the new compacts in 1959. There is also evidence that rapid depreciation of new cars, explained by Akerlof in terms of a 'market for lemons' is also found in used cars sold by dealers, and is likely torepresent the value of dealer and warranty services.